2017
DOI: 10.4081/jphr.2017.834
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed diabetes mellitus and related factors in East Gojjam (NW Ethiopia) in 2016: a community-based study

Abstract: IntroductionCurrently, diabetes is the second most common non-communicable disease (NCD) in Ethiopia. Its burden is 4.8% in this country, even though three quarter of its population live with undiagnosed diabetes mellitus (DM), which causes complications like heart failure, blood vessels, eyes, kidneys and nerves damages. Early detection of DM is vital for a timely intervention to prevent these life threatening complications. The aim of this study was to assess the prevalence of undiagnosed DM and related fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
43
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 15 publications
12
43
4
Order By: Relevance
“…This is probably due to increasing tendency to exercise less or being physical inactive, loss of muscle mass and gaining weight with age. It has been established that the more abundant the fatty tissue in the body, the more resistant are the cells to insulin (Wondemagegn et al, 2017). This finding is similar to findings from Azimi-Nezhad et al in Iran (R & M J, 2008) which showed that further age-related glucose intolerance is related to decreased insulin sensitivity and decreased β-cell function (Shih, Tseng, & Article, 2009).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is probably due to increasing tendency to exercise less or being physical inactive, loss of muscle mass and gaining weight with age. It has been established that the more abundant the fatty tissue in the body, the more resistant are the cells to insulin (Wondemagegn et al, 2017). This finding is similar to findings from Azimi-Nezhad et al in Iran (R & M J, 2008) which showed that further age-related glucose intolerance is related to decreased insulin sensitivity and decreased β-cell function (Shih, Tseng, & Article, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…The pathophysiology of T2DM are complex and interwoven and hence it is important to identify its risk factors. Socio-demographic factors were also found to be associated with prevalence of T2DM such as age (Wondemagegn et al, 2017), gender (Goto et al, 2015), higher BMI (Goto et al, 2015) and co-morbidities such as hypertension (Wondemagegn et al, 2017). This study aims to determine the prevalence of undiagnosed T2DM and to identify its associated factors in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Moreover, among urban dwellers in Ethiopia, about 64.8% of hypertensive subjects and 53.4% of diabetic subjects were estimated to be undiagnosed. 16,17 Previous regional studies used IDF criteria to estimate cardio-metabolic risks and the association of anthropometric indices among bank workers, school teachers, policemen, and other general population. [18][19][20] The IDF recommended Asians and Sub-Saharan Africans (SSA) to use the Europid driven cut off point to define central (abdominal) obesity which is a known indicator and predictor for cardiometabolic risks.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, among urban dwellers in Ethiopia, about 64.8% of hypertensive subjects and 53.4% of diabetic subjects were estimated to be undiagnosed (16,17).…”
mentioning
confidence: 99%